2013
DOI: 10.1177/0907568213488966
|View full text |Cite
|
Sign up to set email alerts
|

Child labour, agency and family dynamics

Abstract: In the last three decades, the development of the artisanal and small-scale mining (ASM) sector has been increasing in the Democratic Republic of Congo (DRC), bringing more and more urban families into this flourishing business sector, and among them, children. This article aims to look at the often unconceivable, and as a result neglected, social agency of children even when they are involved in activities which are, in the international legislation on children's rights, categorized as one of the worst forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…On the one hand, it can operate alongside schooling, deliver immediate financial benefits and allow children to develop skills and operate with some agency. Even studies of more hazardous labour, such as mining (André & Godin, 2013;Okyere, 2013), have found that there are opportunities for children to show initiative, gain respect and contribute to school costs within the context of intergenerational structures. Yet on the other hand, trading is exhausting, frequently displaces schooling and leaves children resentful and conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it can operate alongside schooling, deliver immediate financial benefits and allow children to develop skills and operate with some agency. Even studies of more hazardous labour, such as mining (André & Godin, 2013;Okyere, 2013), have found that there are opportunities for children to show initiative, gain respect and contribute to school costs within the context of intergenerational structures. Yet on the other hand, trading is exhausting, frequently displaces schooling and leaves children resentful and conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…According to Andrea and Godin (2014), the children in Katanga area in Democratic Republic of Congo as social actors demonstrated their agency through contributing towards household income. The authors added that the children exercised their agency in artisanal mining sector besides growing international pressure that the activities were part of the 'worst forms of child labour.…”
Section: Child Agencymentioning
confidence: 99%
“…According to Faber et al [ 16 ], engaging in work hurts children's attendance and performance in school. Balancing both work and school can even lead to dropout rates as children prioritise earning money [ 2 , 17 , 18 ]. However, working and earning money can also provide the means to afford school fees, since education is generally not free [ 19 ].…”
Section: Introductionmentioning
confidence: 99%